Adequacy Of The Basic Handball Techniques Training - Abdul 'Aziz Purnomo Shidiq; Sunardi Sunardi; Agustiyanta Agustiyanta; Satria Yudi Gontara (Nicolaus Copernicus University in Toruń, 2019)
The basic handball technique training for beginners must be in accordance with the physical condition of the player. The intensity and frequency of the exercises are determined precisely so that the exercises are effective and efficient. This research focuses on appropriate training programs so that optimal training results. The target of this research is in the form of training instruments / training programs and research results are published in reputable international journals. The research method used is research and development. The product developed in this research and development refers to the training program that is expected to be a reference in the implementation of basic handball technical training for beginners. From the results of the study, the training program for handball games has a validity of 0.87 so that it can be concluded that the training program for the adequacy of the basic handball technique is effectively used for the beginner athlete training program. Besides that, the training program for the adequacy of basic handball techniques is very much in accordance with the characteristics, growth, development of learners and beginner athletes and is able to make students easier to learn the basic techniques of handball games. The results of the measurement exercise, passing exercises performed 126 times, dribbling exercises performed 238 times, and shooting exercises were carried out 125 times.